Oxidative Stress Markers in Reproductive- Age Women with Iron Deficiency Anemia - Deniz, Levent; Yardim, Meltem; Saltabaş, Mehmet Akif; Arslan, Hilmi Furkan; Akkoc, Ramazan Fazıl; Aral, Hale (My University, 2024)
Aim: During iron deficiency anemia (IDA), increased oxidative stress is accompanied by reduction in antioxidant defense systems and increased lipid peroxidation. We aimed to assess oxidative balance and Deoxyribonucleic Acid (DNA) damage in reproductive-aged women with IDA. Material and Methods: This study included 30 women who had clinically confirmed diagnoses of IDA at the Internal Medicine Polyclinics. Also, we had 30 healthy women compatible with age and body mass index in the control group. Serum levels of 8-hydr oxy-2'-deoxyguanosine (8-OHdG) were quantified via the ELISA technique, while levels of total oxidant status (TOS) and total antioxidant status (TAS) were determined through a spectrophotometrically. Results: Patients with IDA exhibited lower TAS (p=0.001), but higher TOS, 8-OHdG and OSI levels than the controls (p<0.001). TOS had relatively better di agnostic performance with 73.3% sensitivity and 90.0% specificity at a cut-off value 23.7. TOS levels were found to be correlated better with hemoglobin, hematocrit, ferritin, erythrocyte indices, iron, and transferrin saturation. Conclusion: In reproductive-age women with IDA, we showed reduced antioxidant status, and the balance shifted to the oxidative side, including DNA damage.
Keywords: Oxidative Stress; Iron Deficiency Anemia; 8-Hydroxy-2-Deoxyguanosine